2006
DOI: 10.1007/s10038-005-0350-9
|View full text |Cite
|
Sign up to set email alerts
|

A rapid and reliable detection system for the analysis of PMP22 gene dosage by MP/DHPLC assay

Abstract: Charcot-Marie-Tooth disease type 1A (CMT1A) and hereditary neuropathy with liability to pressure palsies (HNPP) are caused by a 1.5-Mb duplication and a deletion at chromosome 17p11.2-12 encompassing the peripheral myelin protein 22 gene (PMP22), respectively. We developed a rapid and reliable detection system for duplications/deletions of the PMP22 gene based on measurement of gene copy number. The method involves amplification of a test locus with unknown copy number and a reference locus of known copy numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 33 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…A wide range of techniques is available for molecular testing of CMT1A/HNPP [18,22,23,[30][31][32][33]. However the faster, cost-effective and reliable method is the analysis of a panel of 15 STRs based on the detection of, at least, two STRs with a trisomic triallelic pattern indicating with certainty the presence of the CMT1A duplication.…”
Section: Discussionmentioning
confidence: 99%
“…A wide range of techniques is available for molecular testing of CMT1A/HNPP [18,22,23,[30][31][32][33]. However the faster, cost-effective and reliable method is the analysis of a panel of 15 STRs based on the detection of, at least, two STRs with a trisomic triallelic pattern indicating with certainty the presence of the CMT1A duplication.…”
Section: Discussionmentioning
confidence: 99%
“…Variations in the quality of the extracted DNA can have major effects on amplification efficiency, with the largest effects seen in the larger products in a multiplex reaction. However, our previous multiplex quantitative genotype analysis studies with HPLC instruments showed that competitive PCR allowed the accurate determination of allele dose variations (32,33,50,51 ).…”
Section: Discussionmentioning
confidence: 99%